Analysis of the Influence of Assessment Center and Transformational Leadership on Career Development with Social Support as Moderation - Nugroho, Robertus Bima Adhi (LPPM Universitas Trunojoyo Madura, 2025)
Objective: The purpose of this study is to determine the influence of the Assessment Center and analyze the influence of Transformational Leadership on the career development of personnel in the DIY Police. In addition, this study also aims to analyze the role of Social Support, both as a factor influencing career development and as a moderator in the relationship between the Assessment Center and Transformational Leadership and the career development of personnel in the DIY Police.Methods: The population in this study amounted to 10,365 personnel in the Yogyakarta Police, with a sample of 151 respondents selected using the Proportional Stratified Random Sampling method so that each strata in the population was proportionally represented. Data collection was carried out through a questionnaire designed on a Likert scale of 1 to 5, where a score of 1 indicated